2004
DOI: 10.1110/ps.04806004
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput automated refolding screening of inclusion bodies

Abstract: One of the main stumbling blocks encountered when attempting to express foreign proteins in Escherichia coli is the occurrence of amorphous aggregates of misfolded proteins, called inclusion bodies (IB). Developing efficient protein native structure recovery procedures based on IB refolding is therefore an important challenge. Unfortunately, there is no "universal" refolding buffer: Experience shows that refolding buffer composition varies from one protein to another. In addition, the methods developed so far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 30 publications
1
89
0
4
Order By: Relevance
“…While this assay measures solubility and not necessarily folding, it has been shown previously that it can be used for estimation of protein folding with high confidence. 28 However, to distinguish between some falsepositive measurements obtained by this approach (Supporting Information Table S1, in gray) (see also Materials and Methods section), we visually re-analyzed each well and found 17 (of 95) visually clear wells, which indicates proper folding of a2N under these conditions (Supporting Information Table S1, in green). Figure 3 shows a summary of these experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this assay measures solubility and not necessarily folding, it has been shown previously that it can be used for estimation of protein folding with high confidence. 28 However, to distinguish between some falsepositive measurements obtained by this approach (Supporting Information Table S1, in gray) (see also Materials and Methods section), we visually re-analyzed each well and found 17 (of 95) visually clear wells, which indicates proper folding of a2N under these conditions (Supporting Information Table S1, in green). Figure 3 shows a summary of these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…27 Thus, correct refolding should be validated by either: (i) circular dichroism spectroscopy, (ii) dynamic light scattering, (iii) SEC, or (iv) functional biochemical and interaction assays. 28 Since first two methods are not compatible with high concentrations of NDSB-256 reagent present in our first preparation, we validated its binding properties after denaturation using surface-plasmon resonance protein-protein interaction assay. In these ''BIAcore TM '' experiments, the purified and refolded a2N was immobilized on a CM4 chip by amine-coupling and the affinity of its interaction with ARNO was studied.…”
Section: Discussionmentioning
confidence: 99%
“…IBs usually consist of almost pure, aggregated proteins which are typically misfolded and thus biologically inactive [19]. In spite of the numerous known reasons for the IB formation, to date there has been no universal technique for efficient folding of the aggregation-prone recombinant proteins [20,21]. Although there are few examples where formation of IBs is highly desirable, such as their use for oral vaccination as an alternate route for the delivery of recombinant antigens for immunization [22], in most cases obtaining a recombinant protein in the soluble form is absolutely crucial.…”
mentioning
confidence: 99%
“…In fact, increasing pH above 8.0 dramatically decreases C cf value. Thus, the previous data obtained from refolding efficacy revealed that solubilization cannot be a true approach to finding the optimum correct protein refolding conditions [16,17]. Data from this study showed that "mixed refolding efficacy", correct folding of interferon, as determined by potency assay were increased simultaneously and was predictable till pH 8.0.…”
Section: Discussionmentioning
confidence: 75%
“…All refolding processes were performed batchwise at 4 °C and the refolding efficiency was determined as the ratio of solubilized protein concentration to the total denatured protein [16,17] at pH 7.0, 7.5, 8.0 and 8.5. The refolding buffer (50 mM Tris-HCl and 50 mM NaCl) was prepared at various pHs (pH 7.0, 7.5, 8.0 and 8.5).…”
Section: Refolding Of Rhifn α-2bmentioning
confidence: 99%